2006
DOI: 10.1111/j.1365-2214.2006.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Change and continuity: childbirth and parenting across three generations of women in the United Arab Emirates

Abstract: The age of first birth has risen for Emirati women and the birth rate may have dropped. Health care has also significantly improved. These results are discussed in relation to government initiatives and physical and social change within the UAE and the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Within this sample five women (4%) were below the age of 20 years. Green and Smith [ 24 ] found that the mean age at which UAE mothers gave birth to their first child increased across three generations from 15.9 to 20.9 years. This decrease in adolescent births is an important change given their associated health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Within this sample five women (4%) were below the age of 20 years. Green and Smith [ 24 ] found that the mean age at which UAE mothers gave birth to their first child increased across three generations from 15.9 to 20.9 years. This decrease in adolescent births is an important change given their associated health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this research study are similar to a previous research study that looked at changes and continuity in childbirth and parenting practices across three generations of women in the United Arab Emirates. It was reported that a factor that was continuous across all three generations, daughters, mothers, and grandmothers, was that most women identified their mothers as the most significant source of information for direction and education after giving birth [20] . It was also reported, however, that some trends were changing across the generations including fewer adolescent births and decreasing birth rates in the younger generation, more daughters giving birth in a hospital setting with a doctor present than their mothers or grandmothers, and significantly fewer daughters were reported to breastfeed than the older generations [20] .…”
Section: Issn 1925-4040 E-issn 1925-4059mentioning
confidence: 99%
“…It was reported that a factor that was continuous across all three generations, daughters, mothers, and grandmothers, was that most women identified their mothers as the most significant source of information for direction and education after giving birth [20] . It was also reported, however, that some trends were changing across the generations including fewer adolescent births and decreasing birth rates in the younger generation, more daughters giving birth in a hospital setting with a doctor present than their mothers or grandmothers, and significantly fewer daughters were reported to breastfeed than the older generations [20] . These findings show that birth practices are changing in the Middle East, most likely due to women becoming more educated, that they are becoming more willing to seek medical help and education as evidenced by the growing trend of delivering with a doctor in a hospital setting, but that more educational programs need to be put in place to teach younger women about beneficial health practices in caring for infants, such as breastfeeding [20] .…”
Section: Issn 1925-4040 E-issn 1925-4059mentioning
confidence: 99%
“…However, gender roles and expectations are changing with rapid social and structural changes and as women start to work more outside the home. Reference [9] note, "Despite the strong commitment to the preservation of cultural traditions, customs and values, the rapid social changes, globalization and strong presence of outside cultures inevitably affect family life processes". One example of a generational shift is an attitudinal one among younger women surrounding traditional cultural expectations connected to the home versus the pursuit of higher education, entering the workforce and obtaining positions in high status jobs and in key decision making positions [9].…”
Section: B Gender Identity In the Emirati Cultural Contextmentioning
confidence: 99%